Narrating North American Borderlands Thomas King, Howard F. Mosher and Jim Lynch - Mayer, Evelyn P. (Mainzer Studien zur Amerikanistik, 2014)
The study centers on the presentation of the North American borderlands in the works of Canadian Native writer Thomas King's Truth & Bright Water (1999), American writer Howard Frank Mosher's On Kingdom Mountain (2007), and American writer Jim Lynch's Border Songs (2009). The three authors describe the peoples and places in the northeastern, middle and northwestern border regions of the USA and Canada. The novels address important border-oriented aspects such as indigeneity, the borderlands as historic territory and as utopian space, border crossing and transcendence, post-9/11 security issues, social interaction along the border, and gender specifics. The interpretation also examines the meaning of border imaginaries, border conceptualizations, and the theme of resistance and subversion.